Natural convection in trapezoidal cavity containing hybrid nanofluid - Mohd Hashim, Muhamad Hasif; Md Arifin, Norihan; Mohamad Som, Ahmad Nazri; Mohamed Ali, Nazihah (Akademia Baru Publishing, 2023)
In this paper, a numerical study of natural convection in a trapezoidal cavity with left heated wall, right cold wall and filled with Cu – Al2 O3 and water hybrid nanofluid. The remaining walls of the cavity are kept at adiabatic. An enhancement in heat transfer is observed with the increase of three different parameters. Based upon the numerical predictions, the effect of Rayleigh number, inclination of the slopping wall, solid volume fraction of nanoparticles on flow and patterns as well tested. We found that acute slopping wall, high Rayleigh number and Cu – Al2 O3 nanoparticles with high concentration are effective to enhance the rate of heat transfer. We also developed a new correlation for the average Nusselt number as a function of the angle, effective thermal conductivity and viscosity as well as Rayleigh number.